Đánh giá kết quả phẫu thuật cắt dạ dày vét hạch D2 nội soi trong điều trị ung thư dạ dày - Hiệp, Phạm Như; Thiện, Hồ Hữu; Vũ, Phạm Anh; Thanh, Phan Hải; Điềm, Trần Sĩ Doãn; Xuân , Nguyễn Thanh; Nhân, Văn Tiến; Trung, Trần Nghiêm; Vỹ, Phạm Trung; Đông, Phạm Xuân; Hiếu, Mai Trung; Đức, Phạm Minh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
-